Balloon sinuplasty versus surgical therapy for chronic rhinosinusitis - Halim, Felicia; Sutikno, Budi (PERHATI-KL, 2025)
Background: An inflammation of the nose and paranasal sinuses is known as rhinosinusitis, and should it persist for 12 weeks or longer, it becomes chronic rhinosinusitis (CRS). Compared to medical therapy, balloon dilatation has been shown to produce statistically significant improvements in symptoms, quality of life, nasal endoscopy scores, and Computed Tomography Paranasal Sinuses (CT-PNS) scores. The outcomes are comparable to those of Functional Endoscopic Sinus Surgery (FESS). Furthermore, it was discovered to be a method that was both safe and bearable. Purpose: To ascertain the role of balloon dilatation in the management of CRS, by comparing the result of Balloon Sinuplasty versus Functional Endoscopic Sinus Surgery. Literature review: A search of Google Scholar over the last 10 years found 375 results, and 14 could used as reference sources. Conclusion: Balloon sinuplasty is a useful method to overcome CRS. Balloon sinuplasty is minimally invasive, avoiding more aggresive and drastic procedures, for cases that are severe and unresponsive to medical treatment.